Keragaman Genetik Tanaman Bawang Merah (Allium Ascalonicum L.) Varietas Bauji Hasil Iradiasi Sinar Gamma 60Co (Generasi 5) - Widyaningtyas, Nanda Widyaningtyas; Moeljani, Ida Retno; Sulistyono, Agus (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2023)
One of the important factors in developing new superior varieties is genetic diversity. Gamma ray irradiation of 60Co is one method of mutation induction. The aim of the study was to find out the dose of irradiation that had the best diversity value in Allium ascalonicum the Bauji variety gamma irradiation 60Co, which consisted of doses of 3 Gy and 4 Gy with 7 replications each using a Randomized Block Design (RBD). The randomization method uses the lottery draw manually. Each treatment required 56 tubers and 1 planter bag contained 4 tubers. Control plants are symbolized by the code "B", plants with a dose of 3 Gy are symbolized by the code "MB 3", and plants with a treatment dose of 4 Gy are symbolized by the code "MB 4". The results showed that the highest plant diversity based on the standard deviation value was in the MB 4 Gy treatment in terms of plant length, tuber number, tuber diameter, wet tuber stover weight, dry tuber weight and tuber weight. While the control produces the highest standard deviation values ​​on the parameters of the number of leaves and the age of flowering. In conclusion, gamma 60Co irradiation had a significant effect on the results of research on the fifth generation of the shallot variety Bauji on the parameters of number of leaves, age of flowering, number of tubers, tuber diameter, wet stover weight of tubers and tuber weight.